Computational and experimental representation of simplified gas turbine bearing chamber geometries - Ahmad H. Attia; Budi Chandra; C.A. Toomer (International Journal of Thermofluids)
Gas turbine engines depend on bearing chambers to support and lubricate moving parts, facilitating movement and heat dissipation. However, achieving a uniform oil coating on bearings remains a challenge, often leading to excessive oil consumption and in-flight oil loss. This research aims to establish accurate experimental and CFD methods to measure the residence time distribution (RTD) in a simplified linear geometry, progressing towards investigations in a cylindrical bearing chamber rig.The first test case uses an inclined rectangular acrylic channel (140 cm length, 3 cm height, 5 cm width) with a 39° slope and flow rates ranging from 0.9 l/min to 2.7 l/min. This simplified geometry allows the study of fundamental oil film dynamics. The experimental setup is complemented by CFD modelling using the Volume of Fluid (VOF) approach with Large Eddy Simulations (LES) to model turbulence.Validation demonstrates high level of accuracy, with film thickness measurements showing an error margin of 0.22 % at lower flow rates and up to 1.7 % at higher velocities. These results confirm the experimental setup and CFD model's reliability, offering a solid foundation for studying multiphase flows in bearing chambers. Future phases will incorporate oil for further validation and refinement.The research question we are asking is: Can the proposed method accurately measure the residence time in an experimental setup?